The Routledge international handbook of valuation and society - Krüger, Anne (Routledge international handbooks, 2025)
The Routledge International Handbook of Valuation and Society builds on the growing research interest in practices of valuation throughout contemporary society, providing an up-to-date overview of the different facets of research in the sociology of valuation.The handbook is divided into five major sections with attention to the treatment of valuation in major areas of sociological theory, as well as its key concepts, discourses, and approaches:Part I: Theoretical perspectivesPart II: Central valuation practices in societal spheresPart III: Cross-cutting valuation practicesPart IV: Valuation and societal changePart V: ReflectionsTogether, the chapters in this book characterize distinctive practices of valuation across different societal spheres, such as education and science, arts and culture, economic life, the environment or digital culture and social media. They also examine the role of valuation in contemporary society and consider the ways it effects social change.This seminal handbook aims at taking stock of the development of the study of valuation with a selection of topics that are important for understanding core perspectives and developments as well as anticipating its future orientation. It will appeal to scholars across the social sciences with interest in the ubiquity of the valuation practices and its effects on social life